New species of the genus Protylenchus Wachek, 1955 (Tylenchida, Allantonematidae) parasitizing Harmonia Axyridis (Pallas, 1773) (Coleoptera, Coccinellidae) in Argentina - Camino, Nora B. (2024)
Protylenchus bonaerensis n. sp. (Tylenchida, Allantonematidae) was found in the Horticultural Belt of Gran La Plata, Argentina. This genus is reported for the first time in our country and a new species is described parasitizing adults of Harmonia axyridis (Pallas, 1773) (Coleoptera, Coccinellidae). This new species is mainly characterized by the males having a thin bursa, females with a non-protuberant vulva, and a short and thin caudal appendage in both sexes. In addition, the life cycle is described.